Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan dan Sikap Ibu Hamil Dalam Pencegahan Anemia Pada Kehamilan Di Wilayah Kerja Puskesmas Kosler - Notesya Astri Amanupunnyo; Lucky Herry Noya (GLOBAL HEALTH SCIENCE, 2021)
Background: Anemia is one of the factors causing increased maternal morbidity and mortality. Indonesia in 2018, prevalence anemia in pregnant women is still high at 48.9%, while Southeast Maluku Regency in 2019 (January-September) is at 22.7% while Puskesmas Kolser is 25.64%. Objective: to determine whether there is an influence of health education on the knowledge and attitudes of pregnant women in the prevention of anemia in the work area of the Kolser Health Center. Method: Pre test and Post test. Samples totaled 28 people. Data analysis: univariate and bivariate analysis the Wilcoxon with deranjat error of 5% (p-value